Early Breastfeeding Initiation (EBFI) Knowledge: Concept Paper - -Pedersen 4 Clara Haruzivishe, Gladys Mugadza 1 , Mathilda Zvinavashe Felicity Zvanyadza Gumbo 3 , Babill Stra (International Journal of Scientific Research and Management (IJSRM), 2017)
The Early breastfeeding initiation means practical giving of the breast milk to the baby soon after delivery that is inthe first hour. Knowledge is defined as a true and justifiable phenomenon. The goal of the researchers in writing inthis paper was to have an in depth description of knowledge regarding early breastfeeding initiation for the purpose ofmeasuring and evaluating performance of nurse midwives performance. Concept analysis model postulated by Walkerand Avant was used in helping describing the concept of interest. The researchers conducted literature search in amonth’s time using, breastfeeding journals, Journals of Nursing Philosophy Cochrane data base, Pub- med andMEDLINE as search engines. Thirty two studies that were found relevant to the concept of interest were included inthe description of EBFI knowledge. Early breastfeeding initiation knowledge was cognitively appraised in almost allstudies.